Pemanfaatan Hasil Hutan Bukan Kayu Terhadap Penghidupan Masyarakat Pesisir Distrik Teminabuan Kabupaten Sorong Selatan - Lestari, Uun; Sri, Putri Meira Shyiang; Ramadani, Soraya; Abago, Maksi (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2025)
This study aims to identify the utilization of Non-Timber Forest Products (NTFPs) in the mangrove ecosystem and analyze their impact on the livelihoods of coastal communities in Teminabuan District, South Sorong Regency. The research was conducted from July to September 2024 using direct interviews with 50 respondents selected through purposive sampling, specifically community members who utilize mangrove resources. Data were collected through inventory to obtain comprehensive information on the types, quantities, and productivity of each NTFP commodity, and then analyzed using qualitative descriptive methods. The results indicate two main categories of NTFP utilization: flora (mangrove leaves, pedada, nipah, coconut, and rattan) and fauna associated with mangroves (honeybees, crabs, clams, ants, catfish, and shrimp). The utilization of NTFPs includes direct consumption, traditional medicine, sales, tourism, and garden creation. Mangroves play an important role as a source of food and livelihood for coastal communities, thus the utilization of NTFPs is carried out sustainably. This study provides baseline data on the potential of mangrove NTFPs in Teminabuan District, supporting sustainable management, community empowerment, forest conservation, and the improvement of coastal community welfare. These findings contribute to local economic development and the conservation of mangrove ecosystems in Southwest Papua.